2021
DOI: 10.35741/issn.0258-2724.56.2.21
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamic of Teachers’ Job Performance

Abstract: Professional teacher performance is the hope of the Indonesian community to teach the next generation well. The research aimed to find out a direct and an indirect effect of exogenous variables toward endogenous variables. The sample research amounted to 360 public high school teachers in Jakarta. Smart-PLS with r > .70 is used to gain the validity and reliability test required to analyze research data. The results showed that there were: direct positive influences of organizational culture and personality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…<0.000. Previous research showed that personality and organisational culture indirectly affect teachers' performance through trust (Virgana, 2021). Then, there was an indirect influence of leadership style on teachers' performance through trust at public universities in Pakistan (A. , of which the study with 233 faculty members who had a large indirect influence (p321) was 0.719 × 0.368 = 0.2646 (26.46%).…”
Section: Intervening Variablementioning
confidence: 97%
See 1 more Smart Citation
“…<0.000. Previous research showed that personality and organisational culture indirectly affect teachers' performance through trust (Virgana, 2021). Then, there was an indirect influence of leadership style on teachers' performance through trust at public universities in Pakistan (A. , of which the study with 233 faculty members who had a large indirect influence (p321) was 0.719 × 0.368 = 0.2646 (26.46%).…”
Section: Intervening Variablementioning
confidence: 97%
“…Likewise, the results of the H5 analysis, namely Tr, have a significant direct effect on TP. That was relevant to the research on junior high school teachers in Jakarta capital city: trust directly effects TP (Virgana, 2021). Then a study was carried out on 130 high school teachers in Sukabumi West Java (Rachmah et al, 2018) and a research was conducted on 326 junior high school teachers in Palembang (Fitria, 2018).…”
Section: Intervening Variablementioning
confidence: 99%
“…In the school setting, JS is a topic that always gets attention because when teachers are not comfortable with their job, it is hard to achieve optimum results (Sembiring & Purba, 2019). It becomes a severe problem in most schools in enhancing the quality of education since every school has developed habits that have been running for years (Virgana, 2021). However, JS may protect workers from stressors (Hoboubi et al, 2017).…”
Section: Organizational Culture (Oc)mentioning
confidence: 99%
“…It yields the quality of work that teachers perform, and that is job performance (Wolomasi, Asaloei, & Werang, 2019;Zikanga et al, 2021). Job performance that teachers are measured in supervision are not limited to preparing teaching and lesson materials, managing students in teaching and learning processes, mastering teaching methods and subject matters (Emengini, Omenyi, & Nwankwo, 2020;Johari, Yean Tan, & Tjik Zulkarnain, 2018;Mandefro, 2020;Uwe & Godwin, 2019;Virgana, 2021). United Nations Educational Science and Cultural Organisation) [UNESCO] (2016), and International Institute for Capacity Buliding in Africa [IICBA] (2017) stipulate that, however, education systems require supervision, elementary education such as lower secondary education need it the most.…”
Section: Introductionmentioning
confidence: 99%